A three-dimensional organoid model recapitulates tumorigenic aspects and drug responses of advanced human retinoblastoma - Duangporn Saengwimol (2019)
© 2018, The Author(s). Persistent or recurrent retinoblastoma (RB) is associated with the presence of vitreous or/and subretinal seeds in advanced RB and represents a major cause of therapeutic failure. This necessitates the development of novel therapies and thus requires a model of advanced RB for testing candidate therapeutics. To this aim, we established and characterized a three-dimensional, self-organizing organoid model derived from chemotherapy-naïve tumors. The responses of organoids to drugs were determined and compared to relate organoid model to advanced RB, in terms of drug sensitivities. We found that organoids had histological features resembling retinal tumors and seeds and retained DNA copy-number alterations as well as gene and protein expression of the parental tissue. Cone signal circuitry (M/L+ cells) and glial tumor microenvironment (GFAP+ cells) were primarily present in organoids. Topotecan alone or the combined drug regimen of topotecan and melphalan effectively targeted proliferative tumor cones (RXRγ+ Ki67+) in organoids after 24-h drug exposure, blocking mitotic entry. In contrast, methotrexate showed the least efficacy against tumor cells. The drug responses of organoids were consistent with those of tumor cells in advanced disease. Patient-derived organoids enable the creation of a faithful model to use in examining novel therapeutics for RB.